Matrix for assessment of activities and participation: Measuring functioning beyond diagnosis in young children with disabilities. (18th July 2013) - Castro, Susana; Pinto, Ana
Abstract: Objective : (i) To study the functioning patterns of young children with disabilities compared with typically developing children, using a new ICF-CY based tool – the Matrix for Assessment of Activities and Participation; (ii) study the factors that predict these functioning patterns. Methods : The MAAP tool was administered to three groups of children: (i) with autism, (ii) with other types of disabilities and (iii) typically developing. Results : Cluster analysis showed that children group according to the severity of their functioning profile and not according to the diagnostic category in which they were classified. Multiple regression analysis showed that a model comprising the environmental factors and the level of engagement in different routines of the child is a good predictor of these children's functioning patterns. Conclusion : These results support a functional approach to disability instead of the traditional medical model approach, underlining the role of engagement and environment in determining functioning.